Expression of DJ-1 in Endometrial Cancer: Close Correlation With Clinicopathological Features and Apoptosis. Issue 6 (1st July 2013) - Shu, Kuanyong; Xiao, Zhongqing; Long, Shenggen; Yan, Jinjin; Yu, Xiaohong; Zhu, Qizhou; Mei, Tong
Abstract : Objectives: DJ-1 was originally cloned as a putative oncogene capable of transforming NIH3T3 cells in cooperation with H-Ras or c-Myc, which has been implicated in the pathogenesis of some solid tumors. The aim of this study was to investigate the expression and clinical significance of DJ-1 in endometrial cancer and study its effect on cell proliferation and apoptosis in endometrial cancer Ishikawa cells. Methods: Reverse transcription polymerase chain reaction and Western blotting were performed to determine the DJ-1 expression in 100 surgical specimens of endometrial cancer tissues, paired tumor-adjacent tissues, and 30 surgical specimens of normal endometrium tissues. The proliferation variety of endometrial cancer Ishikawa cells was determined by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium assay after transfecting the interference plasmid pGPU6/GFP/neo-DJ-1-shRNA into Ishikawa cells. Real-time polymerase chain reaction and Western blotting were used to evaluate the effect of interference plasmid on target gene expression. Apoptosis rate was determined by flow cytometry. Results: DJ-1 expression in endometrial cancer tissues was higher than in tumor-adjacent tissues and normal endometrial tissues. At the same time, it was associated with signs of cancer progression, including differentiation, myometrial invasion depth, and presence of lymph node metastasis. Knocking down DJ-1 promoted the apoptosis of Ishikawa cells. Conclusions: High DJ-1 expression seems to be negatively correlated with apoptosis. Meanwhile, it may be part of the mechanisms for the development, invasion, and metastasis in endometrial cancer.